Blue Shadows Farm : A Novel - Apps, Jerold W., 1934- (Book collections on Project MUSE., 2009)
In the midst of a controversy that disrupts the entire community, Emma looks into her family's past to help her make crucial decisions about the future of its land." "Through the story of the Starkweather family's changing fortunes, and each generation's very different relationship with the farm and the land, Blue Shadows Farm is in some ways the narrative of all farmers and the increasingly difficult challenges they face as committed stewards of the land."--Jacket.